Non-financial human capital disclosure and share price - Mohamat Sabri Hassan,; Marsita Mustafa,; Mara Ridhuan Che Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study is to examine the relationship between disclosure of non-financial human capital information (HCD) and share price of the top 100 companies listed on Bursa Malaysia from financial years 2010 to 2013. Human capital (HC) is considered a valuable asset in a knowledge-based economy. The knowledge and skills possessed by individuals are regarded as a key source of competitive advantage and value creator to companies. Prior research acknowledges the importance of HC information to investors, who may have to rely on disclosures in annual reports when evaluating a company’s future direction, potential, value and prospects. However, companies only disclose limited information on this ‘asset’. In this study, HCD is viewed from the perspective of signalling and efficient capital market theories. Following previous studies, we incorporate HC information and its two components, namely, HC information related to directors and employees, into the Ohlson model. Our study reveals an increasing trend of HCD, and the disclosure is value relevant. Further analysis of the HC information component reveals that both HC information (HC related to directors and employees) are value relevant. These findings are in line with the argument that Malaysian financial analysts and fund managers regard information related to the company’s management and key corporate decision makers as important in investment decision making. The findings of this study are relevant to accounting standard setters in determining the types of HC that should be disclosed in the annual reports because this information can create value for companies. Managers should also pay attention to HC information because such information is value relevant to stakeholders.